Stres Kerja dan Keterikatan Kerja pada Karyawan Swasta: Peran Mediasi Kesejahteraan di Tempat Kerja - Vissy Vandiya; Arum Etikariena (Jurnal Online Psikogenesis, 2018)
Employees who have low work engagement can harm the company, it can be shown by the decreasing of work performance and unproductive. Job stress can impact in decreased attachment of work. Job stress is also a major problem in the individual well-being that can affect the physical, psychological condition of the individual and the organization and also will affect the work engagement. The purpose of this study is to prove the variable of workplace wellbeing as a mediator of job stress variablesÂ with work engagement. The collecting data on the research is by spreading the online questionnaire which is gform and anonymously to the private employees in Jakarta, the ages 25-49 years, with working experience of at least 2 years, and minimum education level is bachelor. The number of respondents who data was processed are 200 people with the number of female respondents are 120 people and men are 80 people. This research uses quantitative research design using mediation analysis from Hayes in PROCESS in SPSS version 23. The scales that researcher used are Job Stress Scale for job stress (IV) with cronbach's alpha = .830, WWBI (Workplace Well-Being Index) for workplace well-being (MV) with cronbach's alpha = .863 and UWES (Utrecht Work Engagement Scale) for work engagement (DV) with cronbach's alpha = .922. The results showed that workplace well-being as a mediation variable with the valueÂ (p0.005, SE =?, CI [-0.2454, -0.0687]